How Large are Earnings Penalties for Self-Employed and Informal Wage Workers? - T. H. Gindling; Nadwa Mossaad; David Newhouse (IZA Journal of Labor & Development, 2016)
This paper examines the earnings penalties and premiums associated with different types of employment in 73 countries. Workers are divided into four categories: non-professional own-account workers, employers and own-account professionals, informal wage employees, and formal wage employees. Approximately half of the workers in low income countries are non-professional own-account workers, and the majority of the rest are informal employees. Fewer than 10 percent are formal employees, and only 2 percent of workers in low income countries are employers or own-account professionals. As per capita gross domestic product increases across countries, there are large net shifts from non-professional own-account work into formal wage employment. Across all regions and income levels, non-professional own-account workers and informal wage employees face an earnings penalty compared with formal wage employees. But in low income countries, this earnings penalty is small, and non-professional own-account workers earn a positive premium relative to all wage employees. Earnings penalties for non-professional own-account workers tend to increase with gross domestic product and are largest for female workers in high income countries. On average, employers and own-account professionals earn a premium compared to employees, although there are important differences across countries and between men and women. In terms of regional differences, earnings premiums for employers and professionals are largest for men in middle income Latin American countries. On the other hand, women employers and professionals do not earn a statistically significant premium compared to employees in any region of the world. These results are consistent with compensating wage differentials and firm quasi-rents playing important roles in explaining cross-country variation in earnings penalties, and raise questions about the extent to which the unskilled self-employed are rationed out of formal wage work in low income countries.
Keywords: J31; O17; 330; Lohnstruktur; Informelle Wirtschaft; Selbstständige; Niedrigeinkommen; Entwicklungsländer